We have to solve the following differential equation given by "x(z^2-y^2)p+y(x^2-z^2)q=z(y^2-x^2)"
Solution:-
"x(z^2-y^2)p+y(x^2-z^2)q=z(y^2-x^2)......"(1)
it is Lagrange's partial differential equation of type
"Pp+Qq=R" ;
So, it has the solution which is
Lagrange's auxiliary equation such that
"\\frac{dx}{P}=\\frac{dy}{Q}=\\frac{dz}{R}"".......(2)"
So,
the auxiliary equation of the equation (1) is
"\\frac{dx}{x(z^2-y^2)}=\\frac{dy}{y(x^2-z^2)}=\\frac{dz}{z(y^2-x^2)}\\\\=\\frac{xdx}{x^2(z^2-y^2)}=\\frac{ydy}{y^2(x^2-\nz^2)}=\\frac{zdz}{z^2(y^2-x^2)}=\\frac{xdx+ydy+zdz}{0}\\\\\\implies xdx+ydy+zdz=0\\\\\\implies \\int xdx+\\int ydy+\\int zdz=0\\\\\\implies x^2+y^2+z^2=c.........(3)"
equation (3) is the general solution of the given equation .
Comments
Leave a comment